Assessment of the predictive power the radiation-induced lymphocyte apoptosis method in prostate cancer patients - Gyöngyvér Orsolya Sándor; Gyöngyi Farkas; Gábor Székely; Péter Ágoston; Kliton Jorgo; László Gesztesi; Tibor Major; Csilla Pesznyák; András Herein; Gábor Stelczer; Dalma Mihály; Georgina Fröhlich; et al. (Scientific Reports)
Abstract Due to the better survival of patients with tumorous diseases, it is increasingly important to predict the side effects of radiotherapy, for which the Radiation-Induced Lymphocyte Apoptosis (RILA) method is proving to be effective in multicentric studies. Prostate cancer is the leading cause of cancer-related deaths among men worldwide, which is usually treated with radiotherapy. We recruited 49 patients with localized prostate cancer and performed RILA measurements before radiotherapy. Patients were treated with CyberKnife (35–40 Gy) or high-dose-rate brachytherapy (1 × 21 Gy). We performed chromosome aberration test for five years and graded side effects, IPSS and QoL questionnaire scores were recorded. We found that RILA% correlated with the IPSS increase (p = 0.0016, r=-0.44), which was confirmed with negative binomial regression (p = 0.0013). The negative predictive value for severe urinary side effects according to the IPSS questionnaire was 87.9% at the lower tertile of RILA values. Chromosome aberrations also correlated with side effects, but when we built models including variables of baseline and treatment characteristics of the patients, RILA, and chromosome aberrations, only RILA predicted a late increase in IPSS score (p < 0.0001, adjusted R2 = 68%). The RILA method was shown to be predictive of urinary side effects especially of patient-reported outcomes.